Dyktatorska pycha przeciwko służbie narodowi. Aksjologiczny wymiar przywództwa na przykładzie prezydentów Rosji i Ukrainy - Mateja, Magdalena (Zeszyty Naukowe Katolickiego Uniwersytetu Lubelskiego Jana Pawła II, 2022)
The article reflects on the issue of leadership in an authoritarian regime and a democratic state and aims to show significant differences between them in the ethical aspect. After the introduction, in which the choice of subject matter was justified, it was explained what a political regime is in the light of the theory of politics, what features define democracy and authoritarianism, and what model of leadership is in force in each of the systems. The next fragment concerns the concept of the authoritarian personality. Indicated values that democratic and authoritarian systems respect, referring both to the behaviour of citizens and to the personality and behaviour of leaders. The principial part of the article concerns the axiology of the styles of leadership and images of the leaders of Russia and Ukraine. The results were obtained through analysis of the selected publications that appeared in the first phase of Russia’s invasion of Ukraine on Polish general information portals and on the Instagram social network. It was shown how politician image differences correlate with differences in the axiological dimension.